Teachers’ Classroom Practice to Develop Student’s English Writing Skills at Primary Level of Bangladesh - Rahman, Md Mehadi; Sarker, Taposhi Rani (Jurnal Pendidikan Progresif, 2019)
Teachers’ classroom practice to develop student’s english writing skills at primary level of Bangladesh. Objectives: The present qualitative study investigates teachers’ classroom practice to develop primary level students English writing skills in Bangladesh, India. Methods: Five-government primary school and five teachers were chosen conveniently from each school in Dhaka. Randomly three English classes of each teacher were chosen to observe their teaching learning practice. The study used a lesson observation protocol and interview protocols as an instrument of data collection. Qualitative data were analyzed thematically. Findings:. Teachers used traditional teaching-learning methods emphasizing students’ rote learning and used Bangla as a medium of instruction. The study also found teachers’ challenges like large class size, extra workload, lack of teaching aids etc. in developing students writing skill at the elementary level. Conclusions: The study explored that teachers’ current practice in Bangladesh does not help students to develop their writing skill at all.Keywords: Teacher classroom practice, english writing skills, primary students, Bangladesh. DOI: http://dx.doi.org/10.23960/jpp.v9.i1.201902